Changing Tetra Pak: from waste to resource. (1st June 2018) - Ma, Yuhui
In recent years, the problem caused by Tetra Pak waste (TPW) has became a topic of great concern to scientists and environmentalists, and commercial companies have also begun to take an interest in developing processes for tackling this issue. In this article, the challenges in the recycling of TPW are described. This article presents the major conclusions of previously published works focussed on the utilisation of TPW for energy and material purposes. The commercial utilisation of TPW is also described. Some suggestions for better recycling of TPW are given in the latter part of this work.